Construction of a reading frame–independent yeast two-hybrid vector system for site-specific recombinational cloning and protein interaction screening - Richard H. Maier; Christina J. Brandner; Helmut Hintner; Johann W. Bauer; Kamil Önder (BioTechniques)
The yeast two-hybrid (Y2H) system is a powerful method to identify protein-protein inter-actions (PPI) in vivo, requiring minimal prior information of the putative interactors. The time and effort required for each experiment can be significantly reduced if the “bait” and the “prey” proteins are cloned into specific recombination-amenable two-hybrid vectors. We describe the construction of a reading frame–independent vector system for Y2H PPI studies. The described vector system knits together the advantages of site-specific recombination cloning with the Y2H system. The produced plasmids enable recombination-based cloning of genes or gene fragments in all possible reading frames into Y2H library vectors. Thus, Y2H screening libraries can be rapidly constructed and will present more amino termini in the correct reading frame. Additionally, advantageous for small-scale Y2H studies, there is no need to know the natural reading frame of the genes of interest, because the bait and prey genes can be transferred into the vectors by a single reaction and are present in all possible reading frames. Since the Y2H system per se is a positive selection system, only pairs of bait and prey genes harboring the correct reading frames will emerge. We tested the new vectors within the Y2H system and demonstrated full functionality without any undesired effects on the Y2H system itself. Besides the vector construction, we investigated the utility of the system for Y2H analysis and demonstrated clearly its practicability in genome-wide Y2H screenings and the advantage of using additional reading-frame Y2H cDNA libraries. We performed a series of genome-wide Y2H library screenings with the human vitamin D receptor protein (VDR) as bait. We investigated: (i) whether more protein interactors are found by using three instead of one reading-frame destination vectors; (ii) how much overlap between the different reading-frame libraries exists; and (iii) the rate of possible additional autoactivators. We conclude that our vectors deliver significantly more interactors and outperform a single reading-frame library. This new system could enable simple and fast large-scale PPI studies and the construction of high-quality screening libraries.